Recurrent tuberculosis among HIV-coinfected patients: a case series from KwaZulu-Natal - Naidoo K (Infection and Drug Resistance, 2018)
Kogieleum Naidoo,1,2 Navisha Dookie,1,3 Kasavan Naidoo,2 Nonhlanhla Yende-Zuma,1 Benjamin Chimukangara,1,3,4 Ambika Bhushan,1 Dhineshree Govender,1 Santhanalakshmi Gengiah,1 Nesri Padayatchi1,2 1Centre for the AIDS Programme of Research in South Africa (CAPRISA), University of KwaZulu-Natal, Durban, South Africa; 2South African Medical Research Council (SAMRC) - CAPRISA HIV-TB Pathogenesis and Treatment Research Unit, Durban, South Africa; 3KwaZulu Natal Research Innovation and Sequencing Platform (KRISP), University of KwaZulu-Natal, Durban, South Africa; 4Department of Virology, National Health Laboratory Service, University of KwaZulu-Natal, Durban, South Africa Background: Recurrent tuberculosis (TB) following TB treatment completion in HIV-infected individuals remains a major public health burden. We assessed the role of various risk factors in mediating the development of recurrent TB and subsequent resistance to antiretroviral therapy and anti-TB drugs. Patients and methods: We analyzed secondary demographic, clinical, and laboratory data from medical records of five HIV-infected TB patients enrolled between 2009 and 2014 in a prospective observational study investigating TB recurrence. Paired clinical isolates of Mycobacterium tuberculosis were typed by IS6110 restriction fragment length polymorphism analysis to determine the mechanism of TB recurrence. Plasma samples were genotyped to determine acquisition of HIV drug resistance mutations on antiretroviral treatment (ART). Results: All five patients were HIV-coinfected, with a previous history of TB infection and prior exposure to anti-TB treatment, and residual lung damage, and demonstrated poor treatment adherence – significant risk factors linked to the development of recurrent TB disease. Furthermore, three of the five patients had multiple episodes of drug-susceptible TB infection with subsequent drug-resistant TB infection. Genotyping of the initial and recurrent M. tuberculosis isolates demonstrated three cases of recurrent TB because of relapse and two because of reinfection. All five patients had no mutations at ART initiation; however, by the end of the study follow-up, all patients developed dual class resistance. Conclusion: This series demonstrates the complexity of recurrent TB in HIV coinfection. We highlight the challenges of managing coinfected patients and the increased propensity for the development of drug resistance. We report on the role of various risk factors mediating the development of resistance and subsequent clinical impact. This report underscores the need for structural clinical and adherence interventions for the management of complex treatment and dosing. Keywords: adherence, TB–HIV coinfection, social risk factors, IS6110 RFLP, drug resistance